A little inflation in the early universe at the QCD phase transition - Boeckel, Moritz Tillmann; Schaffner-Bielich, Jürgen (Physical review letters, 2010)
We explore a scenario that allows for a strong first order phase transition of QCD at a non-negligible baryon number in the early Universe and its possible observable consequences. The main assumption is a quasistable QCD-vacuum state that leads to a short period of inflation, consequently diluting the net baryon to photon ratio to today’s observed value. A strong mechanism for baryogenesis is needed to start out with a baryon asymmetry of order unity, e.g., as provided by Affleck-Dine baryogenesis. The cosmological implications are direct effects on primordial density fluctuations up to dark matter mass scales of Mmax ∼1-10M⊙, change in the spectral slope up to Mmax ∼106-108M⊙, production of strong primordial magnetic fields and a gravitational wave spectrum with present day peak strain amplitude of up to hc(νpeak)∼5×10−15 around νpeak∼4×10−8 Hz.
Gesehen am 01.02.2023